Farm management practices and their effects on the production of sugarcane planters in two mill districts in Batangas - Pelle, Maximo R.
The study was conducted in the area covered by the two mill districts in Batangas from June 2003 to July 2003 to assess and compare the different production operations applied by different planters and factors affecting sugar production to ensure the viability of sugar industry in Batangas. A total of 99 respondents was obtained based on the Slovin's formula i obtaining the sample size. Frequency counts, percentages and means were used for descriptive analysis while chi-square test and simple correlation analysis were used to determine the relationship between the different farm practices and production. The different cultural practices include: land preparation, planting, fertilization, cultivation and weeding, irrigation, pest and disease control, harvesting practices, and ratooning practices. Utilizing some cultural practices, it was found out that they were associated with sugarcane yields in terms of tons cane per hectare (TC/ha). Among the critical factors that showed positive correlations on yield of sugarcane were: the use of tractor in plowing, furrow distance, population density and variety, fertilization, weeding, ratooning and management systems. However, other factors such as soil acidity, pests and diseases, and application of organic fertilizer, generally affect the yield and should be given emphasis. Planters also cited different reasons why their farm lad low yields. They argued that low sugar recovery was due to milling problem in relation to delayed mill programs. Other problems include unfavorable weather, unstable/low price of sugar, scarcity of labor, source of high yielding varieties (HYVs), lack of irrigation facilities and poor roads. To improve the productivity of the farm, modification of present production and management systems should be addressed. It was also found necessary to enhance the use of organic fertilizer as well as formulate a micro-financing scheme to help sugarcane planters in increasing their level of production to have a competitive sugar industry. Considering the technological changes in agriculture, it is found necessary to conduct studies on confluence of factors on technology adoption. This will provide insights in how to hasten effective technology and transfer of ideas, thus speeding up the process of development.